2022
DOI: 10.3390/disabilities2020021
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review on Robotic-Assisted Gait Training in Children and Adolescents with Cerebral Palsy: Training Parameters, Choice of Settings, and Perspectives

Abstract: About 70% of children and adolescents with cerebral palsy experience gait impairments which affect their autonomy and well-being. Robotic-assisted gait training using the Lokomat is particularly promising for rehabilitation as it provides a standardized environment favoring the massive repetition of the movement, in which physical demands are low on the therapist and high training loads can be achieved. As no guidelines exist regarding training protocols and Lokomat settings, the goal of this narrative review … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…In accordance with the works of foreign authors, we have confirmed that RAGT has a positive effect on the motor functions of patients with CP [ 10 , 11 ]. A meta-analysis of studies suggests that gait training has a more significant effect on motor function than conventional rehabilitation [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with the works of foreign authors, we have confirmed that RAGT has a positive effect on the motor functions of patients with CP [ 10 , 11 ]. A meta-analysis of studies suggests that gait training has a more significant effect on motor function than conventional rehabilitation [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although there is some evidence from clinical trials that BWS and Guidance Lokomat settings are important to maximize patient benefits [47], there are currently no guidelines for best practices. This lack of guidelines and the difficulty in defining optimal settings present a major constraint in achieving the expected goals using Lokomat therapy [16,48]. Based on the present results, a combination of high levels of BWS and Guidance tended to mitigate the effect of Lokomat on lower limb kinematics.…”
Section: Discussionmentioning
confidence: 67%
“…There is some, albeit limited, evidence from clinical trials that Guidance and BWS Lokomat settings might be essential to increase the impact of this technology on the gait biomechanics in individuals with neuromotor disorders [13][14][15]. However, the existing literature has not yet sufficiently investigated how Lokomat settings influence lower limb gait patterns [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, specific information about the therapy content is missing in many studies evaluating the effectiveness of physiotherapeutic interventions [ 6 ]. This applies also to modern robotic gait therapies [ 7 , 8 ]. In the case of conventional therapies, reasons for the lack of information include missing tools which can quantify and describe the therapist-patient interactions.…”
Section: Introductionmentioning
confidence: 99%